2023
DOI: 10.1186/s12870-023-04148-4
|View full text |Cite
|
Sign up to set email alerts
|

Plastome variations reveal the distinct evolutionary scenarios of plastomes in the subfamily Cereoideae (Cactaceae)

Abstract: Background The cactus family (Cactaceae) has been reported to have evolved a minimal photosynthetic plastome size, with the loss of inverted-repeat (IR) regions and NDH gene suites. However, there are very limited genomic data on the family, especially Cereoideae, the largest subfamily of cacti. Results In the present study, we assembled and annotated 35 plastomes, 33 of which were representatives of Cereoideae, alongside 2 previously published pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 79 publications
(104 reference statements)
2
19
0
Order By: Relevance
“…We conducted a phylogenetic analysis using 59 shared genes across nine Mammillaria species and one Obregonia species (serving as an outgroup) (Yu et al., 2023 ). In the resulting phylogenetic topology, M. elongata and M. gracilis are distinctly clustered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a phylogenetic analysis using 59 shared genes across nine Mammillaria species and one Obregonia species (serving as an outgroup) (Yu et al., 2023 ). In the resulting phylogenetic topology, M. elongata and M. gracilis are distinctly clustered.…”
Section: Resultsmentioning
confidence: 99%
“…M. elongata (MW553058.1) is distinctively marked in red. The sequences incorporated in the tree are as follows: M. huitzilopochtli (MN517612.1) (Solórzano et al., 2019 ), M. supertexta (MN508963.1) (Solórzano et al., 2019 ), M. solisioides (MN518341.1) (Solórzano et al., 2019 ), M. pectinifera (MN519716.1) (Solórzano et al., 2019 ), M. gracilis (MW553059.1) (Yu et al., 2023 ), M. albiflora (MN517610.1) (Solórzano et al., 2019 ), M. zephyranthoides (MN517611.1) (Solórzano et al., 2019 ), and O. denegrii (MW553062.1) (Yu et al., 2023 ). the scale bar represents a genetic distance of 0.1 substitutions per site.…”
Section: Resultsmentioning
confidence: 99%
“…2022; Qin et al . 2022; Yu et al ., 2023). Cactaceae seem to have the smallest plastome for an obligately photosynthetic angiosperm (∼104-113 kb, Sanderson et al ., 2015; Solórzano et al ., 2019; Amaral et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, beyond their morphological, physiological, and ecological aspects, molecular components also may reveal intriguing traits of cacti. The study of entire cactus plastomes was initiated recently (Sanderson et al, 2015), and since then, it has been revealed that plastomes across cacti have undergone significant changes in gene content, order, and structure compared to canonical angiosperm references (Majure et al, 2019;Solórzano et al, 2019;Köhler et al, 2020;Oulo et al 2020;Amaral et al, 2021;Silva et al, 2021;Almeida et al, 2021;Dalla Costa et al 2022;Qin et al 2022;Yu et al, 2023). Cactaceae seem to have the smallest plastome for an obligately photosynthetic angiosperm (~104-113 kb, Sanderson et al, 2015;Solórzano et al, 2019;Amaral et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of next-generation sequencing and bioinformatics technologies, obtaining plastid genome data is now more affordable and faster than ever before. As a result, plastid genome sequences have been widely and successfully utilized in plant phylogenetic analyses [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%